2011
DOI: 10.1186/1475-2867-11-12
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic properties of Koetjapic acid, a natural triterpene isolated from Sandoricum koetjaoe Merr

Abstract: BackgroundAngiogenesis, the formation of new blood vessels, has become an important target in cancer therapy. Angiogenesis plays an important role in tumor growth and metastasis. Koetjapic acid (KA) is a seco-A-ring oleanene triterpene isolated from S. koetjape. The solvent extract of this plant species was shown previously to have strong antiangiogenic activity; however the active ingredient(s) that conferred the biological activity and the mode of action was not established. Given the high concentration of K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 34 publications
(40 reference statements)
1
27
0
2
Order By: Relevance
“…[12][13][14] Since the n-hexane extract showed potential anti-proliferative activity against a breast cancer cell line, 15) it has been suggested that KA may have potential value as an anti-breast cancer agent. Accordingly, this study has been performed in order to examine the growth inhibitory effect of KA on human breast cancer cells (MCF 7), and to elucidate the mechanism(s) involved in the action of KA.…”
mentioning
confidence: 99%
“…[12][13][14] Since the n-hexane extract showed potential anti-proliferative activity against a breast cancer cell line, 15) it has been suggested that KA may have potential value as an anti-breast cancer agent. Accordingly, this study has been performed in order to examine the growth inhibitory effect of KA on human breast cancer cells (MCF 7), and to elucidate the mechanism(s) involved in the action of KA.…”
mentioning
confidence: 99%
“…These assays provide a valuable data for anti-angiogenesis assessment [37,42]. Endothelial cells tend to be in contact with their neighbouring cells.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitory effect of A3 and B3 was investigated in vivo using fertilized chicken embryo [37]. Fertile eggs were cleaned and kept horizontally with rotation for 3-5 days at 37°C in a humidified incubator to ensure formation of chorioallantoic membrane (CAM) vessel network.…”
Section: Chick Embryo Chorioallantoic Membrane (Cam) Assaymentioning
confidence: 99%
“…TAF273, TAF355 and TAF401 were added at final concentrations of 6.25, 12.5, 25, 50 and 100 μg/ml and the median inhibitory concentrations (IC 50 ) were determined by nonlinear regression analysis of log-concentration-response curves. Similarly, serial concentrations (6.25 to 100 μg/ml) of suramin were used as standard reference (Nassar et al, 2011), whereas distilled water was used as negative control. On day four, the medium was replaced with a fresh one containing the test materials.…”
Section: Ex Vivo Rat Aortic Ring Assaymentioning
confidence: 99%
“…Anti-neovascularization effect of TAF273 was investigated in vivo in chorioallantoic membrane (CAM) assay using chicken embryos as previously reported (Nassar et al, 2011). Five day-old fertilized eggs were obtained from local hatchery.…”
Section: In Vivo Cam Assaymentioning
confidence: 99%